PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA BIRO PENGAWASAN DAN PEMERIKSAAN PT BANK PANIN TBK - Raden Yohanes Luhur (Universitas Mercu Buana, 2014)
Abstract. Decline in the performance of the employee's achievement of businesstargets are not marked with the reporting of audit results in the last three years.This research aims to analyze the influence of leadership, work motivation and thework environment on performance of employees in Biro Pengawasan danPemeriksaan of PT Bank Panin Tbk. The method of research is descriptiveanalysis. The population of the research was the entire employees of BiroPengawasan dan Pemeriksaan PT Bank Panin Tbk which totaled 253 people.Sampling techniques using simple random sampling with the formula slovinfound 155 employees as sample. The methods analysis of this study is multiplelinear regression. F test results show that leadership, work motivation and workenvironment has a positive and significant influence on performance ofemployees. The t-test results show that the leadership of significant and negativeeffect on performance of employees, motivation of working is not significant andnegative effect on performance of employees and work environment a significantand positive effect on performance of employees. Based on the results ofemployees performance analysis can be maximized through increasedpsychological conditions of the work environment, as we reduce overtime.Keywords: Leadership, Work Motivation, Work Environment, EmployeesPerformance.